Modeling the Method of Linear Approximation of Signals in SPLC (Sensor Programmable Logic Controller) - Karimov Abdusamat Ismonovich; Ismanov Mukhammadziyo Abdusamatugli (Research Parks Publishing LLC, 2021)
This paper presents a model of signal approximation using Matlab software. The following design recommendations have been developed for the module to work accurately and correctly. The sensor software program logic controller (PLC) uses a schematic diagram of the differential filter. In evaluating this filter, FDM (Frequency Division Multiplexing) is a technology of multiplexing method that involves combining multiple signals through a common medium.